2019
DOI: 10.1371/journal.pone.0211562
|View full text |Cite
|
Sign up to set email alerts
|

Population dynamics and socio-spatial organization of the Aurignacian: Scalable quantitative demographic data for western and central Europe

Abstract: Demographic estimates are presented for the Aurignacian techno-complex (~42,000 to 33,000 y calBP) and discussed in the context of socio-spatial organization of hunter-gatherer populations. Results of the analytical approach applied estimate a mean of 1,500 persons (upper limit: 3,300; lower limit: 800) for western and central Europe. The temporal and spatial analysis indicates an increase of the population during the Aurignacian as well as marked regional differences in population size and density. Demographi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 47 publications
2
38
0
Order By: Relevance
“…If we apply these results to the hypothesis of Stiner et al (1999), we can predict an increase in the population density of humans from the Aurignacian onwards. This result is consistent with previous studies in the region (Conard et al 2012;Schmidt and Zimmermann 2019).…”
Section: Resultssupporting
confidence: 94%
“…If we apply these results to the hypothesis of Stiner et al (1999), we can predict an increase in the population density of humans from the Aurignacian onwards. This result is consistent with previous studies in the region (Conard et al 2012;Schmidt and Zimmermann 2019).…”
Section: Resultssupporting
confidence: 94%
“…Our results, along with the high concentration of other large, close-by sites (e.g., Barca and Kechnec localities and other findspots), indicate that by 34 ka B.P., the Aurignacian technocomplex was well established along the Hornád Valley as part of an expanding population in eastern central Europe with the site reflecting a potential seasonal population (Schmidt and Zimmermann 2019;Svoboda 2006) in an area where abundant resources were located within a modest walking radius (< 5 h; Hauck et al 2018). If the purported habitation structures, storage pits, and other "site furniture" from Barca (I, II, and III), Seňa I and Tibava are indeed supported (which is still controversial); they would also strongly intimate a sustained occupation at least on a semi-regular basis (Binford 1979).…”
Section: Discussionsupporting
confidence: 59%
“…The decrease in human presence in Southern Iberia was already noted by Straus et al [14], and the increase in sites from the Early to Late Iberomaurusian was recognized in Linstädter et al [25]. Numerous studies have demonstrated the fragility of Upper Palaeolithic groups in Europe due to very low population densities [7,83,84], resulting in highly vulnerable settlement structures and land use patterns.…”
Section: Discussionmentioning
confidence: 95%